2021
DOI: 10.1007/s10841-021-00307-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of abandonment and restoration of Mediterranean meadows on butterfly-plant interactions

Abstract: Both the intensification and abandonment of traditional agricultural practices are known to be major threats to biodiversity worldwide, above all in industrialized countries. Although land abandonment in particular has a negative effect on the diversity of both plant and insect communities, few studies have ever analysed these two groups together and none has yet examined the effect on plant-insect interactions using a network approach. In view of the notable decline of pollinator insects reported in past deca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Studies have found warmer temperatures leading to higher population abundance in most butterfly species in the UK (Roy et al 2001) and a mixture of butterfly abundance responses to temperature in Spain (Stewart et al 2020). In contrast, Isaac et al (2011) found butterfly density in England was generally lower in regions with higher temperatures, and Colom et al (2021) found warmer summers were associated with smaller butterfly populations on the Spanish island of Menorca. In Massachusetts USA, butterfly populations near their species' northern range limits are generally increasing, and populations near their species southern range limits are generally decreasing (Breed et al 2012, Michielini et al 2021.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have found warmer temperatures leading to higher population abundance in most butterfly species in the UK (Roy et al 2001) and a mixture of butterfly abundance responses to temperature in Spain (Stewart et al 2020). In contrast, Isaac et al (2011) found butterfly density in England was generally lower in regions with higher temperatures, and Colom et al (2021) found warmer summers were associated with smaller butterfly populations on the Spanish island of Menorca. In Massachusetts USA, butterfly populations near their species' northern range limits are generally increasing, and populations near their species southern range limits are generally decreasing (Breed et al 2012, Michielini et al 2021.…”
Section: Discussionmentioning
confidence: 98%
“…While it is becoming increasingly rare, objectively problematic metrics for phenological patterns such as first or last observations are still used by at least some ecologists (Colom et al 2022021, Fric et al 2020). For many types of data sets, observations of first and last events are known to be biased, as the day of first or last observation depends in part on population size and detectability (Miller‐Rushing et al 2008, Van Strien et al 2008, Inouye et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, these approaches include flower bagging experiments, observations of floral visitation, and pollen identification from insect specimens as described above. These approaches are rarely combined, and pollination studies are dominated by observational methods and quantitative literature reviews, typically with a focus on flower visitation observations for estimating network parameters (Yamaji and Ohsawa, 2016;Colom et al, 2021;Mendes et al, 2022). Visitation network studies typically consist of observation periods in which the researcher observes and records the visitors to a particular plant in an allotted time period.…”
Section: Data Collection and Pollen Analysismentioning
confidence: 99%
“…Essential Biodiversity Variables (EBVs) covered by every monitoring programme as primary and secondary targets, defined as in [7]. The CBMS has made significant contributions to knowledge on the effect of global change on Mediterranean butterflies, including the effects of climate change on phenology and population dynamics [62][63][64][65], the significance of current landscape changes on butterfly communities [66][67][68] and, more generally, a robust assessment of butterfly trends at the regional scale [47,69,70]. From a practical perspective, data from the CBMs have been used to evaluate the effects of several managing practices [68,71,72].…”
Section: Scientific Questions For Tracking Biodiversity Changementioning
confidence: 99%
“…The CBMS has made significant contributions to knowledge on the effect of global change on Mediterranean butterflies, including the effects of climate change on phenology and population dynamics [62][63][64][65], the significance of current landscape changes on butterfly communities [66][67][68] and, more generally, a robust assessment of butterfly trends at the regional scale [47,69,70]. From a practical perspective, data from the CBMs have been used to evaluate the effects of several managing practices [68,71,72]. Moreover, the assembled dataset has provided invaluable information in various autoecological studies [73][74][75][76] and has also been used in combination with data from other similar schemes to reveal ecological patterns and responses at the continental level [13,77,78].…”
Section: Scientific Questions For Tracking Biodiversity Changementioning
confidence: 99%